2001
DOI: 10.1097/00000539-200111000-00052
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Tramadol, Amitriptyline, and Meperidine for Postepidural Anesthetic Shivering in Parturients

Abstract: This study was performed to compare the antishivering and side effects among tramadol, amitriptyline, and meperidine for the treatment of postepidural anesthetic shivering in parturients. Both tramadol and meperidine show a significantly faster response rate in the treatment of shivering when compared with amitriptyline. Tramadol had a less frequent incidence of somnolence than meperidine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
119
2
7

Year Published

2003
2003
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 144 publications
(142 citation statements)
references
References 26 publications
10
119
2
7
Order By: Relevance
“…It also modulates the activity of nucleus median raphe acting centrally on the m opioid receptors predominately with minimum effects on k and d receptors. The antishivering effect of tramadol is mediated via serotonergic of noradrenertic receptor or both [10][11][12]. Tramadol in a dose of 1mg/ kg iv has been shown to be effective in the treatment of postoperative shivering.…”
Section: Discussionmentioning
confidence: 99%
“…It also modulates the activity of nucleus median raphe acting centrally on the m opioid receptors predominately with minimum effects on k and d receptors. The antishivering effect of tramadol is mediated via serotonergic of noradrenertic receptor or both [10][11][12]. Tramadol in a dose of 1mg/ kg iv has been shown to be effective in the treatment of postoperative shivering.…”
Section: Discussionmentioning
confidence: 99%
“…Mean arterial blood pressure and heart rates were recorded every 15 minutes with noninvasive blood pressure monitoring and pulse oximetry. Shivering involving whole body was checked every 5 minutes during surgery and at recovery room by a 4 point rating score system (0: none, 1: mild fasciculation in face or neck, 2: visible tremor in more than one muscle group, 3: shivering involving whole body) for 2 hours [6,7,19,20] . In case of shivering score ≥ 2 intravenous pethidine 0.5 mg/kg was given.…”
Section: Methodsmentioning
confidence: 99%
“…It increases oxygen consumption, lactic acidosis, carbon dioxide production and catecholamine release [4][5][6][7] . One of the primary causes of post anesthesia shivering (PAS) is hypothermia which is due to direct inhibition of body thermoregulatory mechanisms by anesthetics, decreased metabolism, patient's exposure to cold environment of operating rooms and body cavity exposure of postoperative shivering [11] .…”
Section: Introductionmentioning
confidence: 99%
“…Em estudo realizado em 220 pacientes com o objetivo de identificar a dose eficaz de meperidina para o tratamento de tremores, Crossley 76 concluiu que 0,35 mg.kg -1 é a menor quantidade necessária para tratar tremor pós-operató-rio de forma satisfatória. O uso do tramadol para tratamento de tremores tem sido feito nos últimos anos, e a sua eficácia é semelhante à da meperidina segundo alguns estudos 77 . O nefopam é uma benzoxacina analgésica de ação central que reduz os tremores sem comprometer a ventilação, com mínimos efeitos sedativos e com eficiência comprovada.…”
Section: Tratamento Dos Tremores Pós-operatóriosunclassified
“…In a study with 220 patients aiming at identifying the effective dose of meperidine for the treatment of tremors, Crossley 76 concluded that 0.35 mg.kg -1 is the smallest dose necessary to treat adequately postoperative tremors. Tramadol has also been used in the past few years to treat tremors and, according to some studies, its efficacy is similar to that of meperidine 77 . Nefopam is a central-acting analgesic benzoxacin that reduces tremors without affecting ventilation, with minimal sedation, and proven efficacy.…”
Section: Treatment Of Postoperative Tremorsmentioning
confidence: 99%